Cu:Al Nano catalyst for selective hydrogenolysis of glycerol to 1,2-propanediol - Mane, Rasika B.; Hengne, Amol M.; Ghalwadkar, Ajay A.; Vijayanand, Subramanian; Mohite, Pravin H.; Potdar, Hari S.; Rode, Chandrashekhar V. (Catalysis Letters, 2010)
Non-chromium Cu:Al nano catalyst prepared by simultaneous co-precipitation and digestion method without any template or stabilizer, showed three times higher activity than the bulk Cu-Cr catalyst for hydrogenolysis of glycerol in both isopropanol and water solvents, with the selectivity to 1,2-Propanediol (1,2-PDO) as high as 91% at 493 K and H(2) pressure of 7 MPa in 5 h. XRD pattern showed the presence of Cu(+) species in the activated Cu: Al nano catalyst. Although Cu(+) is catalytically inactive in glycerol hydrogenolysis reaction, the presence of Cu(+) helps to stabilize the particle size in a narrow range of 7-11 nm by inhibiting the sintering of copper particles under reaction conditions.
Keywords: 1; 2-Propanediol; Cu:Al nano catalyst; Glycerol; Selective hydrogenolysis

Continuous dehydration and hydrogenolysis of glycerol over non-chromium copper catalyst: laboratory-scale process studies - Mane, Rasika B.; Rode, Chandrashekhar V. (Organic Process Research & Development, 2012)
A non-chromium Cu:Al catalyst was developed for glycerol dehydration under N-2 atmosphere to acetol and hydrogenolysis to 1,2-propanediol (1,2-PDO). Among the various copper-based catalysts screened in this work, Cu:Al-1 catalyst showed the highest activity and acetol selectivity in water medium, whereas transfer hydrogenation in 2-propanol as the reaction medium led to the formation of 1,2-PDO (10-38%). The same catalyst was also found to catalyze the direct hydrogenolysis of glycerol to 1,2-PDO. Time on stream activity (TOS) of our Cu:Al-1 catalyst for both continuous dehydration and hydrogenolysis of glycerol was found to be 400 h with an average glycerol conversion of 90% and 65%, respectively. Maximum acetol selectivity was 55% while 1,2-PDO selectivity was 91% in dehydration and hydrogenolysis reactions separately. Effects of various reaction conditions on conversion, selectivity, and global rates of the two processes were also investigated.